Early biochemical effects of velmanase alfa in a 7‐month‐old infant with alpha‐mannosidosis. Issue 1 (10th July 2020) - Santoro, Lucia; Zampini, Lucia; Padella, Lucia; Monachesi, Chiara; Zampieri, Stefania; Dardis, Andrea; Cordiali, Rosanna; Galeazzi, Tiziana; Catassi, Carlo
Abstract: Alpha mannosidosis is an ultrarare pathology with variable phenotypic manifestations, characterized by the deficiency of lysosomal alpha mannosidase which causes accumulation of neutral oligosaccharides. Until recently, the hematopoietic stem cell transplantation was the only clinical feasible therapeutic option. Only in 2018, the European Medicines Agency's committee approved the recombinant enzyme velmanase alfa for long‐term treatment of non‐neurological manifestations in mild and moderate forms of alpha‐mannosidosis. In this study, the very early biochemical effects of enzyme replacement therapy in in a 7‐month‐old patient with alpha‐mannosidosis were described. Velmanase alpha was administered as supporting therapy awaiting for hematopoietic stem cell transplantation, the treatment chosen for the patient because of the early onset form. The results showed that the enzyme replacement therapy was able to reduce the content of three different mannosyl‐oligosaccharides monitored by tandem mass spectrometry after 2 months of treatment. In particular, the mean relative changes from baseline values were −67% in urine and −53% in serum at the latest observation. The study also showed that the enzymatic activity detected in serum 1 week after the first infusion was four times higher than the normal values and constant in the following points of observation. These findings led us to assume that velmanase alfa might be biologically active in this young patient.